REKAM MEDIK PASIEN BERBASIS HANDWRITING MENGGUNAKAN ANDROID - Affandi, Luqman; Widarti, Dinny Wahyu (WIDYA TEKNIKA, 2014)
Medical Records is a file that contains the patients identity documents, examination results, and action to patients in health facilities. The development of the patients health can be controlled through this document. If doctors want to see the history of the disease and the treatment that has been done before, but it takes a long time because the medical record of the file is still in the form of notes on paper with the need to open a medical record notes one by one. This process will be longer if the medical record of the file is missing. To overcome the problems that needed replacement paper medical record technology, and the technology can operate as easy as using paper. Namely the application of medical records using handwriting technology. The medical records without the need for operator assistance, so that the medical record can be done more quickly and reduce the risk of data loss due to data stored on the server. Patient Medical Record history can be searched directly through the application. These applications will be expanded with SDLC systems development methods. The process is carried Anaslisis Issues Medical Record, Modeling and Design System Interface Application, coding Applications, and Implementation. Keywords: Rekam Medik, Handwriting, dan Android